The Impact of Green Human Resource Management on Organizational Environmental Performance: The Mediating Role of Employee Pro-Environmental Behavior - Dedi Joko Hermawan; Hidayatul Hikmah (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study examines the impact of Green Human Resource Management (GHRM) on organizational environmental performance, with employee pro-environmental behavior as a mediating variable, in the context of PT Surabaya Industrial Estate Rungkut (SIER). A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a sample of 80 employees. Data were collected through structured questionnaires and analyzed to assess both direct and indirect relationships among variables. The results indicate that GHRM has a positive and significant effect on organizational environmental performance and significantly influences employee pro-environmental behavior. Furthermore, employee pro-environmental behavior is found to have a positive effect on environmental performance and partially mediates the relationship between GHRM and organizational outcomes. This study contributes theoretically by integrating organizational practices and individual behavioral mechanisms into a comprehensive model of environmental performance, particularly within an industrial context in a developing country. Practically, the findings suggest that organizations should enhance sustainability outcomes by strengthening GHRM practices and fostering employee engagement in pro-environmental activities. The study is limited by its sample size and single organizational focus; therefore, future research is recommended to include broader contexts and additional variables. Overall, this research highlights the importance of aligning human resource strategies with environmental objectives to achieve sustainable organizational performance.